The mechanistic landscape of Lytic transglycosylase as targets for antibacterial therapy. (December 2022) - Martinez-Bond, Elizabeth A.; Soriano, Berliza M.; Williams, Allison H.
Abstract: Lytic transglycosylases (Ltgs) are glycan strand cleaving enzymes whose role is poorly understood in the genesis of the bacterial envelope. They play multiple roles in all stages of a bacterial life cycle, by creating holes in the peptidoglycan that is necessary for cell division and separation. Here, we review recent advances in understanding the suitability of Ltgs as antibacterial drug targets. We specifically highlight a known inhibitor bulgecin A that is able to inhibit the function of structurally diverse Ltgs, as well as synergize with beta-lactams to improve its efficacy in antibiotic insensitive strains. Discovery of new antibiotics or new targets has been challenging. These studies could provide a viable path toward designing broad-spectrum inhibitors that targets Ltgs. Graphical abstract: Image 1